A case control study to evaluate the electrolyte abnormalities in asphyxiated neonates - Ahmed, Nazeer; Sushma, Uppalapati; Thobbi, A. N. (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal asphyxia is a hypoxic condition in new-born and leads to encephalopathy as well as electrolyte disturbances and imposes significant morbidity and mortality. So, the current study was performed to assess the electrolyte abnormalities among asphyxiated neonates as compare to controls. Methods: 50 neonates have beendistributedas2 groups, with case group with 25 cases and 25 cases in neonates group depending on the variables namely Apgar score, fetal heart rates and meconium-stained liquor after baby delivery. Serum sodium, potassium and calcium ranges has been estimated; compared between the groups. In asphyxiated neonates based on the severity the electrolytes levels were also compared. Results: The prevalence of birth asphyxia seems to be higher among male new born (64%). The sodium and calcium ranges has been decreased among asphyxiated babies when associated with control group and it was significant 129.78±4.18 vs 140.76±9.76; 8.12±2.87 vs 10.42±3.12 mg/dl). The electrolyte disturbances were higher in HIE stage 3 of high severity as compared to HIE stage I and II. Conclusions: Electrolyte imbalances namely hyponatremia, hyperkalemia, hypocalcemia were found to be communal in asphyxiated neonates. Thus, proper monitoring is required to prevent the morbidity and mortality among the neonates.